Leading Organizations Through the Stages of Grief: The Development of Negative Emotions Over Environmental Change. (February 2017) - Friedrich, Elmar; Wüstenhagen, Rolf
This conceptual article theorizes about the effect of emotions of individual organizational leaders during a period of sustainability-related upheaval within an industry. To illustrate the effect of emotions, it proposes to draw on the model of five stages of grief by Elisabeth Kübler-Ross, a conceptual framework describing terminally ill patients' responses to their impending death. The authors adapt Kübler-Ross's taxonomy and use anecdotal evidence from grieving top managers of energy companies in response to the nuclear phase-out in Germany. The article conceptualizes the influence of emotions in the decision-making process of key agents in response to institutional pressures in their field. The article suggests that focusing on emotional influences will add an important dimension to the analysis of sustainability strategies, and discuss implications for further research at an individual and organizational level.